Peppermint [videorecording (DVD)] - Garner, Jennifer, 1972-; Gallagher, John, Jr., 1984-; Ortiz, John (Universal Pictures Home Entertainment, 2018)
A revenge story focusing on a young mother who finds herself with nothing to lose, and is now going to take from her enemies the very life they took from her.